THE PROVISION OF A TEMPORARY NATIONAL DATA CENTER AS A REFLECTION OF BOUNDED RATIONALITY IN THE ELECTRONIC BASED GOVERNMENT SYSTEM (SPBE) - Mohamad Nur Syamsi Rizal; Sidik Pramono (RADJA PUBLIKA, 2026)
This research explores the implementation of Indonesia digital governance policies, particularly the Electronic-Based Government System, One Data Policy, and the development of The National Data Center (NDC) and The Temporary National Data Center (TNDC). Drawing on the theoretical framework of Bounded Rationality the analysis highlights how the government’s decision-making process adapts to constraints of limited resources, information asymmetry, and administrative complexity. The findings indicate that while the establishment of a permanent NDC remains the ideal solution for achieving full data integration and security, pragmatic approaches such as the TNDC scheme have enabled continued digital transformation in the public sector. The integration of government data has improved transparency, accountability, and inter-agency coordination, thereby enhancing the efficiency and responsiveness of public services. Regulatory frameworks including Presidential Regulations No. 95/2018, No. 39/2019, and No. 27/2022 have provided a robust institutional foundation to ensure data governance, cybersecurity, and citizen trust. By this research Indonesia incremental approach demonstrates how adaptive policy strategies can effectively advance digital transformation amid institutional and infrastructural limitations.